2019
DOI: 10.1111/jgh.14665
|View full text |Cite
|
Sign up to set email alerts
|

Significant effects of late evening snack on liver functions in patients with liver cirrhosis: A meta‐analysis of randomized controlled trials

Abstract: Background and Aim Reducing post‐absorptive (fasting) phase by eating late evening snacks (LESs) is a potential intervention to improve substrate utilization and reverse sarcopenia. This study analyzed the results of published randomized controlled trials and controlled clinical trials to evaluate the effects of LES on liver function of patients with cirrhosis. Methods A meta‐analysis was conducted. The search strategy included electronic database searches, and 300 articles were searched. Eight of these articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 28 publications
0
58
0
1
Order By: Relevance
“…It should be emphasised that the optimal daily energy intake should not be lower than 35 kcal/kg/d (in non‐obese individuals) and protein intake should not be lower than 1.2‐1.5 g/kg/d (amount of protein > 1.5 g/kg/d should be ingested to replenish malnourished and/or sarcopenic state) . The daily intake should be divided into frequent small meals and/or snack (5‐6 times/d) and, of importance, late evening oral nutritional supplementation containing ≥ 50 g of complex carbohydrates must be included, as it has been shown to be more effective on substrate utilisation and nitrogen retention than daytime calorie supplementation alone . Several studies have demonstrated that late evening snack or meal is an effective intervention to prevent and to reverse sarcopenia in cirrhosis, resulting in an improvement in quality of life and also liver functions .…”
Section: Management Of Malnutrition and Sarcopenia In Cirrhosismentioning
confidence: 99%
See 2 more Smart Citations
“…It should be emphasised that the optimal daily energy intake should not be lower than 35 kcal/kg/d (in non‐obese individuals) and protein intake should not be lower than 1.2‐1.5 g/kg/d (amount of protein > 1.5 g/kg/d should be ingested to replenish malnourished and/or sarcopenic state) . The daily intake should be divided into frequent small meals and/or snack (5‐6 times/d) and, of importance, late evening oral nutritional supplementation containing ≥ 50 g of complex carbohydrates must be included, as it has been shown to be more effective on substrate utilisation and nitrogen retention than daytime calorie supplementation alone . Several studies have demonstrated that late evening snack or meal is an effective intervention to prevent and to reverse sarcopenia in cirrhosis, resulting in an improvement in quality of life and also liver functions .…”
Section: Management Of Malnutrition and Sarcopenia In Cirrhosismentioning
confidence: 99%
“…1,4 The daily intake should be divided into frequent small meals and/or snack (5-6 times/d) and, of importance, late evening oral nutritional supplementation containing ≥ 50 g of complex carbohydrates must be included, as it has been shown to be more effective on substrate utilisation and nitrogen retention than daytime calorie supplementation alone. 1,4,[88][89][90] Several studies have demonstrated that late evening snack or meal is an effective intervention to prevent and to reverse sarcopenia in cirrhosis, resulting in an improvement in quality of life and also liver functions. [88][89][90] Notably, when prescribing a low sodium (<2-3 g/d) diet, the increased risk of even lower food intake (due to unpalatability) should be balanced against its moderate advantage in the treatment of ascites.…”
Section: Nutritional Support and Bcaa Supplementationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue, Chen et al conducted meta-analysis of eight published randomized control comprising 341 patients (167 in LES groups and 174 in control groups) and controlled clinical trials to evaluate the effects of LES on patients with cirrhosis. 4 The eight studies demonstrated that LES intervention had significant effects for liver biochemical parameters such as albumin, ammonia and prothrombin time, serum AST, and ALT. Studies on clinical signs of liver dysfunction showed lower occurrence rates of ascites and hepatic encephalopathy than in the control group.…”
Section: Late Evening Snackmentioning
confidence: 99%
“…In the present issue of the Journal of Gastroenterology and Hepatology, Chen et al . reported results of meta‐analysis of studies which investigate the effects of the late evening snack (LES) on liver function in patients with cirrhosis . Recent studies of the effect of nutritional managements for cirrhotic patents on their quality of life and life prognoses include the following.…”
mentioning
confidence: 99%